Fatal Outcome in a Kidney-Pancreas Transplant Recipient With COVID-19 - Suwanwongse, Kulachanya (Cureus, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a highly contagious pathogen causing the novel coronavirus disease 2019 (COVID-19), the ongoing unprecedented pandemic in 2020. SARS-CoV-2 primarily targets the respiratory systems, so acute respiratory distress syndrome is the major cause of death. Clinical courses of COVID-19 are variable and unpredictable, while some epidemiologic and clinical factors have been found to have a negative impact on the disease prognosis. Despite a growing report on clinical characteristics and prognosis of patients with COVID-19, the data in the special population, including transplant recipients, is still limited. Herein we report on the clinical features and fatal outcome of COVID-19 in a dual pancreas-kidney transplant recipient (with failure of the pancreas graft). Our case illustrates the similarities and differences of the COVID-19 disease course between transplant recipients and the general population. We proposed that the pre-existing T-cell dysfunction from the long-term use of immunosuppressive agents in organ transplant recipients adversely affects COVID-19 prognosis and worsens COVID-19 mortality.